Pembelajaran STEM Konteks Kopi Terhadap Kemampuan Pemecahan Masalah Siswa Materi Statistika - Nun Latifa; Novi Susanti; Indah Widyaningrum (STKIP Subang, 2026)
This study aimed to determine the effect of STEM learning in the coffee context on students’ problem-solving ability in Statistics for grade X students at SMA Negeri 01 Tanjung Sakti Pumu. This research used a quantitative approach with an experimental method. The subjects consisted of 22 students with an average score of 81.727%. Data were collected through documentation and tests. The results showed that students’ ability to understand problems was in the very good category (99%), planning problem-solving strategies was in the good category (86%), implementing the plans was in the good category (87%), and reviewing the solutions was also in the good category (77.3%). It can be concluded that the problem-solving ability.